Perceived Organizational Support for Innovation and Innovative Work Behavior: The Role of Leader-Member Exchange - Anis Eliyana; Muchtar, Darmawati; Dwijo Waskito; Suryarini, Diah Yovita (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study are to investigate the effect of perceived organizational support (POS) for innovation on innovative work behavior (IWB), and the mediating role of leader-member exchange (LMX) in the relationship between perceived organizational support and innovative work behavior. The samples of this study are 31 lecturers taken among 40 respondents that filled out the questionnaires in Faculty of Civil and Planning Engineering Technology Sepuluh November (ITS), Surabaya, particularly taken from Architecture, Interior and Product Design Department. This study used Partial Least Square (PLS) for the data analysis. The results show that the perceived organization support for innovation has significant positive effect on innovative work behavior and leader-member exchange. Similar result also find that leader-member exchange has positive effect on innovative work behavior although the result is insignificant. This implies that the influence of perceived organizational support for innovation on innovative work behavior was not mediated by leader-member exchange. In conclusion, the ITS should improve the perceived organizational support for innovation toward innovative work behavior. It is also expected that this study can contribute to the leadership literature by exploring one of the processes through which the supervisor-subordinate relationship and perceived organizational support contributes to organizational success, specifically innovative work behavior.